2019
DOI: 10.1073/pnas.1900125116
|View full text |Cite
|
Sign up to set email alerts
|

Severe haze in northern China: A synergy of anthropogenic emissions and atmospheric processes

Abstract: Regional severe haze represents an enormous environmental problem in China, influencing air quality, human health, ecosystem, weather, and climate. These extremes are characterized by exceedingly high concentrations of fine particulate matter (smaller than 2.5 µm, or PM2.5) and occur with extensive temporal (on a daily, weekly, to monthly timescale) and spatial (over a million square kilometers) coverage. Although significant advances have been made in field measurements, model simulations, and laboratory expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
489
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 713 publications
(531 citation statements)
references
References 159 publications
17
489
1
1
Order By: Relevance
“…Hence, the present review paper provides a synopsis of the new findings in those papers, centering on CAPI. The chemical formation and transformation of haze pollution, as well as the influence from emissions and meteorological conditions in East Asia, have recently been reviewed systematically by others (e.g., An et al, 2019;, so the present work is an important complement to them. This paper is structured as follows: section 2 summarizes the major methodologies employed in the papers of the current special issue, including groundbased, airborne, and spaceborne observations, as well as numerical models; section 3 reviews the studies pertaining to aerosol physicochemical properties; section 4 discusses the research about process-level understanding of aerosol effects on cloud and precipitation properties; section 5 reviews the large-scale effects of aerosols on the regional climate over East Asia; and section 6 summarizes the new findings in the current special issue and future challenges and directions.…”
Section: Motivation and Backgroundmentioning
confidence: 95%
“…Hence, the present review paper provides a synopsis of the new findings in those papers, centering on CAPI. The chemical formation and transformation of haze pollution, as well as the influence from emissions and meteorological conditions in East Asia, have recently been reviewed systematically by others (e.g., An et al, 2019;, so the present work is an important complement to them. This paper is structured as follows: section 2 summarizes the major methodologies employed in the papers of the current special issue, including groundbased, airborne, and spaceborne observations, as well as numerical models; section 3 reviews the studies pertaining to aerosol physicochemical properties; section 4 discusses the research about process-level understanding of aerosol effects on cloud and precipitation properties; section 5 reviews the large-scale effects of aerosols on the regional climate over East Asia; and section 6 summarizes the new findings in the current special issue and future challenges and directions.…”
Section: Motivation and Backgroundmentioning
confidence: 95%
“…Although great strides have been made in the past decades, the estimation of SOA in the atmosphere is still highly uncertain (An et al, 2019; Ehn et al, 2014; Kanakidou et al, 2005; Shrivastava et al, 2017; Volkamer et al, 2006). It remains difficult to quantify the contribution of precursors in the ambient environment.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia emission control has received a lot of attention especially for controlling the severe haze pollution in China. Recently, An et al (2019) indicated a 50% reduction in ammonia yielded a 10% reduction in PM 2.5 in a haze event in North China. NO 3 − will be further enhanced if ammonia emissions are not reduced, and the reduction in ammonia emissions is beneficial to PM 2.5 control for most regions .…”
Section: Introductionmentioning
confidence: 99%
“…NO 3 − will be further enhanced if ammonia emissions are not reduced, and the reduction in ammonia emissions is beneficial to PM 2.5 control for most regions . Recently, An et al (2019) indicated a 50% reduction in ammonia yielded a 10% reduction in PM 2.5 in a haze event in North China. Liu et al (2019) also implied that a 50% reduction in ammonia emissions with a 15% reduction in sulfur dioxide and nitrogen oxides can reduce PM 2.5 by 11% − 17%.…”
Section: Introductionmentioning
confidence: 99%